THE INFLUENCE OF FASHION INVOLVEMENT AND SHOPPING LIFESTYLE ON IMPULSE BUYING IN SHOPEE E-COMMERCE WITH POSITIVE EMOTION AS AN INTERVENING VARIABLE AMONG STATE UNIVERSITY STUDENTS IN PALEMBANG CITY - Desi Pitri Yunita; Heri Junaidi; Chandra Zaky Maulana (CV. Cendikiawan Muda Sriwijaya, 2025)
This study was motivated by the fact that students at Raden Fatah Islamic University in Palembang tend to make impulsive purchases due to high exposure to promotions through live streaming features on the Shoppe e-commerce platform. Promotions such as big discounts, flash sales, and attractive designs trigger emotional impulses and spontaneous shopping decisions. This phenomenon is closely related to consumptive lifestyles, interest in fashion, and positive emotions while shopping, considering that Shopee is the largest e-commerce platform with the highest number of visitors. This study aims to analyze the influence of Fashion Involvement and Shopping Lifestyle on Impulse Buying on Shopee E-Commerce with Positive Emotion as an Intervening Variable (Study of State University Students in Palembang). This study uses a quantitative approach. The population of this study consists of state university students in Palembang who have shopped on Shopee, with a sample size of 160 respondents. The data collection technique uses primary data in the form of a questionnaire using a Likert scale. The data analysis technique in this study uses Outer Model Analysis, Inner Model Analysis, Bootstrapping, and Path Coefficients. The results of this study indicate that (1) Fashion Involvement does not affect Impulse Buying, (2) Shopping Lifestyle affects Impulse Buying, (3) Fashion Involvement affects Positive Emotion, (4) Shopping Lifestyle affects Positive Emotion, (5) Positive Emotion affects Impulse Buying, (6) Fashion Involvement affects Impulse Buying through Positive Emotion, and (7) Shopping Lifestyle affects Impulse Buying through Positive Emotion.